1998
DOI: 10.1128/iai.66.4.1654-1659.1998
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Antitoxic Activities among Children with Clinical Episodes of Malaria

Abstract: Healthy Gambian children, children with clinical Plasmodium falciparum malaria, and children with asymptomatic P. falciparum infections were studied to investigate whether antitoxic activities may contribute to protection against malarial symptoms. Markers of inflammatory reactions, soluble tumor necrosis factor receptor I, and C-reactive protein were found in high concentrations in children with symptomatic P. falciparummalaria compared with levels in children with asymptomatic P. falciparum infections or in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 22 publications
2
5
0
Order By: Relevance
“…This finding has been reported by many studies (e.g. McGuire et al 1996;Hurt et al 1994;Jakobsen et al 1998). CRP was also positively correlated with parasite density (r= 0.46, n= 434, P <0.001) ( fig.…”
Section: Factors Associated With Absenteeismsupporting
confidence: 87%
“…This finding has been reported by many studies (e.g. McGuire et al 1996;Hurt et al 1994;Jakobsen et al 1998). CRP was also positively correlated with parasite density (r= 0.46, n= 434, P <0.001) ( fig.…”
Section: Factors Associated With Absenteeismsupporting
confidence: 87%
“…Our PYT data for the year 2007 aligns with the findings of Bouvier et al [15], Genton et al [26] and Dicko et al [19]. Our finding can be explained by the fact that anti-toxic activity generally decreases with increasing age in children [36]. Since fever is parasite toxin dependent and level of toxin is directly related to parasite biomass in the host [37], there is likelihood of infants requiring higher parasite burden to elicit fever due to malaria than older children.…”
Section: Discussionsupporting
confidence: 91%
“…In the work of Bouvier et al [15], geometric mean parasite densities of 3448 pf/uL and 918 pf/uL were found in children aged 1-3 y and 4-5 y respectively. The higher parasite density in infants and young children might be due to the poor anti-parasite immunity in this age group [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Generally, antimalarial immunity is acquired gradually and thus improves with age in children [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRP as a protein is mainly regulated at the transcriptional level, induced by cytokines [32]. It is a marker of inflammatory reactions and cytokine activation [33], which is produced early after infection [34]. CRP is reported to be a critical element during a majority of infections [35] and there is a correlation of CRP and NO in some infections including leishmaniasis.…”
Section: Introductionmentioning
confidence: 99%